Murray Leinster the life and works - Stallings, Billee J., 1928- (McFarland & Co., 2011)
"Will F. Jenkins, known to science fiction fans by his penname Murray Leinster, was among the most prolific American writers of the 20th century. This biography chronicles Leinster's private and literary life from his first writings and early pulp magazines, through the golden age of science fiction in the 1930s through the 1950s, to his death in 1975"--Provided by publisher.